O duplo na perspectiva da literatura fantástica nos contos de Cristina Fernández Cubas - Amorim, Suelen Marcellino Izidio de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The double has been long present in literature and it became a recurring theme since the Romantic period in the 18th century. Many writers have highlighted the double in their works. As the double has been represented in a variety of ways and acquired varied meanings, it has been subject of several studies. This thesis results from a research that had as main goal to perform, from the perspective of the fantastic literature, an interpretative analysis of the double in the work of the contemporary Spanish writer Cristina Fernández Cubas (1945 - ). To do such analysis, we have selected the following short stories: Lúnula y Violeta (1980), En el hemisferio sur (1983), Helicón (1990), La mujer de verde (1994), La fiebre azul (2006) and El moscardón (2006). During the research we have studied the double in literature, the fantastic and the short story genre. Such studies constitute the basis for our interpretative analysis of the above short stories. As theoretical framework, we have used the works: Juan Herrero Cecilia (2000, 2011), Sigmund Freud (1976), Nádia Battella Gotlib (1998), Carl Gustav Jung (1987), Rebeca Martín López (2006), Otto Rank (1939), David Roas (2011), Clément Rosset (2008) and Teresa Martín Taffarel (2001). From the final remarks of this study, we draw attention to: the constant approach of the creative process of the writer by means of the double and the discussions, inserted throughout the text, on both the double and the fantastic genre. Relating to the double, it appears in several ways, but the subjective double prevails. In most cases, in the analyzed short stories, the double is related to the question of identity and associated with the fantastic

O duplo há muito tempo está presente na literatura e passou a ser mais recorrente a partir do século XVIII, no Romantismo. Vários escritores produziram obras que dão destaque ao tema. E, por estar na literatura das mais diversas formas, trazendo os mais diversos significados, o duplo proporcionou e proporciona, consequentemente, diversos estudos. Esta dissertação é resultado de uma pesquisa que teve por objetivo principal a realização da análise interpretativa do duplo, sob perspectiva da literatura fantástica, na obra da escritora contemporânea espanhola Cristina Fernández Cubas (1945-). Para a realização da análise, foi feita a seleção dos seguintes contos: Lúnula y Violeta (1980), En el hemisferio sur (1983), Helicón (1990), La mujer de verde (1994), La fiebre azul (2006) e El moscardón (2006). No desenvolvimento da pesquisa, foi feito o estudo do duplo na literatura, do fantástico e do gênero conto. Tais estudos, serviram de base para a realização das análises interpretativas dos contos. Em relação ao suporte teórico, citamos, em especial: Juan Herrero Cecilia (2000, 2011), Sigmund Freud (1976), Nádia Battella Gotlib (1998), Carl Gustav Jung (1987), Rebeca Martín López (2006), Otto Rank (1939), David Roas (2011), Clément Rosset (2008) e Teresa Martín Taffarel (2001). Das considerações finais do trabalho, destacamos: a constante presença da abordagem do processo criativo do escritor por meio da figura do duplo e, inseridas em meio à narrativa, discussões e reflexões sobre o tema do duplo e o gênero fantástico. Em relação ao duplo, este apresenta-se das mais diversas formas, prevalecendo o duplo subjetivo. Em suma, na maior parte dos contos analisados, o tema está relacionado à questão da identidade e associado ao fantástico
Keywords: Fernández Cubas, Cristina, 1945- Crítica e interpretação; Literatura fantástica - História e crítica - Séc. XX; Contos fantásticos espanhóis; Duplo (Literatura); Romantismo; Fantasy literature